Framework Proposal for DevOps Maturity Evaluation - Levita, Carlos de Amorim (2018)
This paper proposes a framework for evaluating the DevOps maturity in organizations. The methodology was based on a literature review from which a theory was developed that sought to relate the main DevOps practices. For each of them, some research constructs were defined, which are precisely the objects to be measured by this model. Through a structure based on questions with graded answers, it is possible to indicate how much the unit of analysis that is being evaluated adheres to a DevOps approach in the development and implementation of applications. Therefore, the main contribution of this work is the DevOps maturity evaluation framework that can be easily replicated and, because of that, may be used by several companies to map possible improvement points in their implementation of the DevOps perspective for software development.